Analysis of international experience in organizing the system of armaments and military equipment public procurement - Tkach , Ivan; Syniavskyi , Vladimir; Yakovchuk , Eugene; Rudy , Mikhail; Korchytsky , Vladimir; Sergienko , Roman (Social Development and Security, 2021)
The experience of organizing the system of armaments and military equipment public procurement in the USA, Great Britain, France, Germany. These are states to have a modern leading highly developed defense industry and are active participants in the world arms market. The general characteristics of the arms procurement system, features of the legal framework construction for the organization of public procurement, parliamentary and public control over them, ways to identify suppliers, sustainable trends in simplification and flexibility of public procurement systems, and measures to support state producers (suppliers) of goods, works, services.